1981
DOI: 10.1111/j.1365-2311.1981.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

A 9‐year study of the life cycle of Ephemera danica Müll. (Ephemeridae: Ephemeroptera) in the River Lambourn, England

Abstract: Abstract. 1. The life cycle of the mayfly, Ephemera danica, was studied on two contrasted sites on the River Lambourn between 1971 and 1979.2. Quantitative samples of nymphs were taken on the five major biotopes of the river bed, gravel, silt, Ranunculus, Berula and Callitriche. Exposed areas of gravel and silt held significantly lower densities of nymphs than the three macro‐phytes with their underlying substrata. The sandy substratum underlying beds of Berula frequently held significantly higher densities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 7 publications
2
12
1
Order By: Relevance
“…The riparian cover of woody shrubs & seedlings was a significant factor influencing the mayfly Ephemera danica. Riparian vegetation cover might be important in providing shelter from wind for adults, although Wright et al (1981) did not find higher nymph density on a river site with trees compared to one with open grassland. However, further examination of the distribution of mayflies may reveal closer associations with riparian habitat quality/ecotone integrity as this is likely to be a key requirement for adult life stages.…”
Section: Discussioncontrasting
confidence: 55%
“…The riparian cover of woody shrubs & seedlings was a significant factor influencing the mayfly Ephemera danica. Riparian vegetation cover might be important in providing shelter from wind for adults, although Wright et al (1981) did not find higher nymph density on a river site with trees compared to one with open grassland. However, further examination of the distribution of mayflies may reveal closer associations with riparian habitat quality/ecotone integrity as this is likely to be a key requirement for adult life stages.…”
Section: Discussioncontrasting
confidence: 55%
“…In agreement with results from other long-term studies (Wright, 1978;Wright, Hiley & Berrie, 1981;Colbo, 1985), variations between years are common in stream invertebrate communities. The stability in the population densities appears rather weak.…”
Section: Equilibrium Of Stream Invertebrate Communitysupporting
confidence: 81%
“…Wright et al (1981) in a 9-year study of the mayfly Ephemera danica Mtiller in an English chalk river observed important annual variations and suggested that good climatic conditions during the flight period were critical for good recruitment. Other papers report annual variations in depteran populations (Chironomidae, Wright, 1978 ;Drake, 198 1;and Simuliidae, Colbo, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…For example, cooler geographic regions at higher latitudes cause delayed development and reduced numbers of generations per year in ephemerid mayflies (Clifford, 1982;Corkum & Hanes, 1992;Newbold et al, 1994) and various other aquatic insects (Ward & Stanford, 1982;Sweeney, 1984;Brittain, 1990). Detailed studies on a riverine ephemerid mayfly, Ephemera danica, showed that it has a 2 or 3-year life cycle in Europe depending on its location in France (Thibault, 1971), Sweden (Svensson, 1977), Spain (AguayoCorraliza et al, 1991), and Britain (Wright et al, 1981;Tokeshi, 1985). A lacustrine burrowing mayfly, Hexagenia limbata, also showed a linear relationship between voltinism and latitudinal location in North America (Heise et al, 1987).…”
Section: Discussionmentioning
confidence: 96%